Global burden of chronic kidney disease and risk factors, 1990–2021: an update from the global burden of disease study 2021 - Lanhui Wang; Yining He; Chao Han; Chao Han; Peiqi Zhu; Yaping Zhou; Ruijie Tang; Weiming He (Frontiers in Public Health)
IntroductionThe burden of chronic kidney disease (CKD) varies across regions. This study provides comprehensive global, regional, and national estimates of total CKD and CKD due to four specific etiologies from 1990 to 2021.MethodsData were extracted from the 2021 Global Burden of Disease study, categorized by sex, 20 age groups, 204 countries or territories, and 5 sociodemographic index (SDI) regions. Age-standardized incidence rates (ASIRs), age-standardized prevalence rates (ASPRs), age-standardized death rates (ASDRs), age-standardized disability-adjusted life year rates (ASDARs) and risk factor burdens for total CKD and four etiology-specific types were analyzed. Temporal trends were assessed using the estimated annual percentage change.ResultsIn 2021, CKD remained a significant global burden, with 673 million prevalent cases and 1.5 million deaths, primarily due to metabolic risk factors. The fastest growth in the ASPR and ASIR occurred in the middle-SDI regions, whereas the highest ASDR and ASDAR were observed in low-SDI regions. From 1990 to 2021, global ASIR increased for CKD caused by all four specific etiologies. The ASDR and ASDAR increased for CKD due to type 2 diabetes, glomerulonephritis, and hypertension, whereas there was a decline in CKD due to type 1 diabetes.DiscussionBetween 1990 and 2021, CKD-related disability-adjusted life years (DALYs) and deaths increased substantially, with type 2 diabetes and hypertension accounting for half of the etiology-specific DALYs in 2021. Effective health policies are urgently needed to address CKD risk factors and implement prevention strategies.